2016
DOI: 10.1902/jop.2016.160046
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Surgical Periodontal Therapy Reduces Saliva Adipokine and Matrix Metalloproteinase Levels in Periodontitis

Abstract: Adipokines may contribute to the breakdown of periodontal tissue in periodontitis by stimulating the expression of proinflammatory cytokines and MMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…CSF‐1 shows similar trends to MMP‐8. The present findings support previous reports of the potential of whole saliva to mirror periodontal inflammation through the presence of molecules associated with periodontal pathogenesis 6‐8,10 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CSF‐1 shows similar trends to MMP‐8. The present findings support previous reports of the potential of whole saliva to mirror periodontal inflammation through the presence of molecules associated with periodontal pathogenesis 6‐8,10 …”
Section: Discussionsupporting
confidence: 92%
“…In patients with periodontitis, however, CSF‐1 and MMP‐8 stayed high after treatment despite improvement in clinical periodontal parameters. Published works by others on salivary MMP‐8 after treatment of periodontitis in patients differ depending on the time point for follow‐up 8 , 33 , 34 . MMP‐8 levels in gingival crevicular fluid (GCF) during wound healing after surgery were found increased at 2 and 4 weeks compared with baseline and decreased between 2 and 12 weeks 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunomodulatory effects of chemerin might be both inflammatory and anti‐inflammatory. The potential inflammatory function of chemerin in periodontitis might be underlined by the fact that the levels of chemerin in gingival crevicular fluid and saliva decreased after periodontal therapy. In synovial fibroblasts, chemerin increased expression of toll‐like receptor 4 and of the chemokine (C‐C motif) ligand 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers often investigate the levels of such biological markers in the periodontium in atempts to gauge the severity of periodontal disease and monitor periodontal treatment outcomes [33]. Recent studies reported that a hypoxic environment may upregulate proinlammatory cytokines and MMPs' expression from host cells during periodontal disease [34]. The idea was that hypoxia further encourages lipopolysaccharide (LPS)-induced TNF-α, interleukin-1β, and interleukin 6 (IL-6) expressions via LPS toll-like receptor (TLR) interaction that, in turn, activates the nuclear factor kappa B (NF-κB) pathway in human PDL cells upon exposure to the aforementioned Gram-negative bacterial surface component [35][36][37].…”
Section: Hypoxia and Chronic Periodontal Inlammationmentioning
confidence: 99%